Thermostable xylanase-aided two-stage hydrolysis approach enhances sugar release of pretreated lignocellulosic biomass. (June 2018) - Long, Lingfeng; Tian, Dong; Zhai, Rui; Li, Xun; Zhang, Yu; Hu, Jinguang; Wang, Fei; Saddler, Jack
Graphical abstract: Highlights: Thermostable xylanase-aided two-stage hydrolysis improve biomass deconstruction. High-temperature xylanase treatment increased cellulose accessibility to cellulase. High-temperature xylanase treatment facilitated biomass slurry viscosity reduction. Abstract: One of the challenges in biorefinery is the still too much enzyme involved in the saccharification of the cellulosic component. High-temperature hydrolysis with thermostable enzyme showed promise. In this study, a temperature-elevated two-stage hydrolysis, including xylan "coat" removal at high-temperature by thermostable xylanase (Xyn10A) from Thermotoga thermarum DSM 5069 followed with saccharification step by commercial cellulase, was introduced to improve biomass deconstruction. Results showed that high-temperature xylanase treatment considerably increased cellulose accessibility/hydrolyzability towards cellulases, with smoothed fiber surface morphology. Comparing with commercial xylanase (HTec) treatment at 50 °C, thermostable Xyn10A pre-hydrolysis at 85 °C was able to achieve a slightly better improvement of cellulose hydrolysis with much lower xylanase loading (about 5 times lower than HTec). It appeared that the increased temperature during thermostable xylanase treatment facilitated biomass slurry viscosity reduction, which exhibited more benefits during hydrolysis of various steam pretreated substrates at increased solid content (up to 10% w/w).